Final efficacy, immunogenicity, and safety analyses of a nine-valent human papillomavirus vaccine in women aged 16–26 years: a randomised, double-blind trial. Issue 10108 (11th November 2017) - Huh, Warner K; Joura, Elmar A; Giuliano, Anna R; Iversen, Ole-Erik; de Andrade, Rosires Pereira; Ault, Kevin A; Bartholomew, Deborah; Cestero, Ramon M; Fedrizzi, Edison N; Hirschberg, Angelica L; Mayrand, Marie-Hélène; Ruiz-Sternberg, Angela Maria; et al.
Summary: Background: Primary analyses of a study in young women aged 16–26 years showed efficacy of the nine-valent human papillomavirus (9vHPV; HPV 6, 11, 16, 18, 31, 33, 45, 52, and 58) vaccine against infections and disease related to HPV 31, 33, 45, 52, and 58, and non-inferior HPV 6, 11, 16, and 18 antibody responses when compared with quadrivalent HPV (qHPV; HPV 6, 11, 16, and 18) vaccine. We aimed to report efficacy of the 9vHPV vaccine for up to 6 years following first administration and antibody responses over 5 years. Methods: We undertook this randomised, double-blind, efficacy, immunogenicity, and safety study of the 9vHPV vaccine study at 105 study sites in 18 countries. Women aged 16–26 years old who were healthy, with no history of abnormal cervical cytology, no previous abnormal cervical biopsy results, and no more than four lifetime sexual partners were randomly assigned (1:1) by central randomisation and block sizes of 2 and 2 to receive three intramuscular injections over 6 months of 9vHPV or qHPV (control) vaccine. All participants, study investigators, and study site personnel, laboratory staff, members of the sponsor's study team, and members of the adjudication pathology panel were masked to vaccination groups. The primary outcomes were incidence of high-grade cervical disease (cervical intraepithelial neoplasia grade 2 or 3, adenocarcinoma in situ, invasive cervical carcinoma), vulvar disease (vulvar intraepithelial neoplasia grade 2/3, vulvar cancer), and vaginal disease (vaginal intraepithelial neoplasia grade 2/3, vaginal cancer) related to HPV 31, 33, 45, 52, and 58 and non-inferiority (excluding a decrease of 1·5 times) of anti-HPV 6, 11, 16, and 18 geometric mean titres (GMT). Tissue samples were adjudicated for histopathology diagnosis and tested for HPV DNA. Serum antibody responses were assessed by competitive Luminex immunoassay. The primary evaluation of efficacy was a superiority analysis in the per-protocol efficacy population, supportive efficacy was analysed in the modified intention-to-treat population, and the primary evaluation of immunogenicity was a non-inferiority analysis. The trial is registered withClinicalTrials.gov, numberNCT00543543 . Findings: Between Sept 26, 2007, and Dec 18, 2009, we recruited and randomly assigned 14 215 participants to receive 9vHPV (n=7106) or qHPV (n=7109) vaccine. In the per-protocol population, the incidence of high-grade cervical, vulvar and vaginal disease related to HPV 31, 33, 45, 52, and 58 was 0·5 cases per 10 000 person-years in the 9vHPV and 19·0 cases per 10 000 person-years in the qHPV groups, representing 97·4% efficacy (95% CI 85·0–99·9). HPV 6, 11, 16, and 18 GMTs were non-inferior in the 9vHPV versus qHPV group from month 1 to 3 years after vaccination. No clinically meaningful differences in serious adverse events were noted between the study groups. 11 participants died during the study follow-up period (six in the 9vHPV vaccine group and five in the qHPV vaccine group); none of the deaths were considered vaccine-related. Interpretation: The 9vHPV vaccine prevents infection, cytological abnormalities, high-grade lesions, and cervical procedures related to HPV 31, 33, 45, 52, and 58. Both the 9vHPV vaccine and qHPV vaccine had a similar immunogenicity profile with respect to HPV 6, 11, 16, and 18. Vaccine efficacy was sustained for up to 6 years. The 9vHPV vaccine could potentially provide broader coverage and prevent 90% of cervical cancer cases worldwide. Funding: Merck & Co, Inc.